(untitled) (Global Journal of Human-Social Science, 2021)
Introduction: Gender violence is "any act or intense that origins a hurt or physical, sexual or psychological suffer against women, including threats of these acts, coercion or arbitrary privation of freedom, in public or private life". The specific needs of these women are multidimensional, so it demands sanitary interventions that take into account biological, psychological and social aspects. Goal: To identify the nursing interventions for the attention of gender violence. Methodology: To carry out a bibliographic research in the scientific databases: PubMed, Cuidatge, Cuiden and ScienceDirect. Analysis of the results obtained on the research and the comparison of them in order to answer the expressed questions. Results: The final results of the bibliographic research are 23 articles. Discussion: The nursing interventions involve embracing the victims. To ask open ended questions. Trying to understand and reinterpret the symptoms. To give a biopsychosocial assessment.